In Vitro Study of Antiamoebic Activity of Methanol Extracts of Argemone mexicana on Trophozoites of Entamoeba histolytica HM1-IMSS - Elizondo Luévano, Joel Horacio; Castro Ríos, Rocío; Sánchez García, Eduardo; Hernández García, Magda Elizabeth; Vargas Villarreal, Javier; Rodríguez Luis, Osvelia Esmeralda; Chávez Montes, Abelardo (Hindawi Publishing Corporation, 2018)
Infections caused by parasites in humans represent one of the main public health concerns. Amoebiasis, a parasitic infection caused by Entamoeba histolytica (E. histolytica), is considered endemic in Mexico, where Argemone mexicana (A. mexicana) has been used in traditional medicine to treat intestinal parasitic diseases. ,e objective of this work was to evaluate the potential biological activity of A. mexicana on E. histolytica. For this purpose, a methanolic extract was prepared from A. mexicana leaves, and a differential fractionation was carried out with solvents of different polarities. The inhibitory capacities of the extract and its fractions were evaluated in vitro using HM1-IMSS, a strain of Entamoeba histolytica. A. mexicana extract was found to have a growth-inhibiting activity for E. histolytica, showing IC50 = 78.39 μg/mL. The extract was characterized phytochemically, and the methanolic extract fractions were analyzed by liquid chromatography (HPLC) and mass spectrometry (MS). Berberine and jatrorrhizine were present in the active fractions, and these compounds may be responsible for the antiparasitic activity. The identification of amoebicidal activity of A. mexicana on E. histolytica gives su pport to the traditional use. Further studies withberberine and jatrorrhizine will be carried out to understand the mechanism involved.